A COMPARATIVE STUDY OF IN-VITRO NITRIC OXIDE SCAVENGING ACTIVITY OF BALOFLOXACINVS PRULIFLOXACIN - Ranka, Puja; Vp, Karthik (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: To compare the free radical scavenging activity and antioxidant potentials of balofloxacin versus prulifloxacin. Methods: Nitric oxide (NO) radical scavenging activity was determined using the method of Garret (1964). Sodium nitroprusside in aqueous solution at physiological pH spontaneously generates NO, which interacts with oxygen to produce nitrite ions which can be determined by the use of Griess ilosvay reaction. 2 mm of 10 mm sodium nitroprusside in 0.5 ml phosphate buffer saline (pH 7.4) was mixed with 0.5 ml prulifloxacin and balofloxacin at various concentrations and the mixture incubated at 25Â°C for 150 minutes. From the incubated mixture 0.5 ml was taken out and added into 1.0 ml sulfanilic acid reagent (30 in 20% glacial acetic acid) and incubated at room temperature for 5 minutes. Finally, 1.0 ml naphthylethylenediamine dihydrochloride (0.1% w/v) was mixed and incubated at room temperature for 30 minutes. The resultant absorbance was recorded at 540 nm usinga spectrometer. The percentage inhibition was calculated using the formula: Percentage inhibition = Â Abscontrol Â âˆ’ AbssampleÂ Â Ã—Â 100 Abscontrol Results: At concentration of 10, 20, 30, and 40 Âµg/ml percentage inhibition observed with prulifloxacin and balofloxacin was 40.94, 53.09, 66.25,88.06 and 34.49, 49.09, 60.42, and 73.14, respectively. Conclusion: Thus, this in vitro study suggests that both prulifloxacin and balofloxacin possess antioxidant properties. At the lower doses both the drugs show similar antioxidant profile, while at the higher doses the antioxidant potential of prulifloxacin is significantly high than balofloxacin. However, the preference of selecting one over the other depends on the indication as well as the risk-benefit ratio. Keywords: In vitro, Nitric oxide, Prulifloxacin, Balofloxacin.